Potential Use of the Maillard Reaction for Pharmaceutical Applications: Gastric and Intestinal Controlled Release Alginate-Albumin Beads - Mouhamad Khoder (Pharmaceutics, 2019)
In this study, bovine serum albumin (BSA) and alginate (ALG) conjugates were synthesized by the Maillard reaction in order to evaluate their potential to develop controlled release drug delivery systems. The progress of the Maillard reaction was evidenced using ultraviolet (UV) absorbance, determination of BSA remaining free amino groups, and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). BSA-ALG conjugates possessed enhanced and tunable viscosity, foamability and foam stability. Foam generated from BSA-ALG conjugate solution was used to prepare floating gastroretentive calcium ALG beads. Unlike traditional ALG beads, BSA-ALG foam beads were able to float and sustain the ciprofloxacin (CIP) release in gastric medium. Interestingly, intestinal beads made of ALG, BSA-ALG physical mixture and BSA-ALG conjugate resulted in different release rates and orders of indomethacin (IND) in simulated intestinal fluids; while beads based on a physical mixture of BSA-ALG resulted in a first order sustained release profile, both systems based on ALG and BSA-ALG conjugate displayed zero order sustained release profiles with IND being released at a slower rate from the conjugate beads.